Role of thermal fluid dynamics in alloying element distribution and weld porosity in powder feeding-based laser welding of Al alloy. (5th May 2020) - Lei, Zhenglong; Wu, Shibo; Cao, Bingqi; Li, Bingwei; Liang, Jingwei; Hu, Xue; Chen, Yanbin
Graphical abstract: Highlights: A 3D model incorporating the powder transport, laser heating, and molten pool dynamics in an integrated manner is developed. Effects of different melt flow behaviors on the distribution of alloying element are investigated. Three necessary steps for bubble formation and migration are concluded. A Glass-Al composite sample is designed to observe keyhole and molten pool behaviors. The obtained results are of great significance to providing a guidance for process optimization. Abstract: This work develops a model incorporating the powder transport, laser heating, and molten pool dynamics to describe the mixing process of alloying element and reveal the mechanisms of bubble dynamics in powder feeding-based laser welding. Simulation results show that the different roles of recoil pressure: driving the molten metal flow at the rear part of keyhole in partial penetration and maintaining the stable keyhole profile in full penetration, are responsible for the difference between their melt flow behaviors. Driven by the melt flow, the alloying element transport path can be generalized as the shallow areas, the rear areas, the central and bottom areas in partial penetration. It permits a relatively uniform silicon distribution. However, two vortices rotating in the opposite direction in full penetration results in a higher concentration of Si in the upper part. Meanwhile, we conclude three steps for the bubble dynamics: bulge formation, bubble formation, bubble being captured by re-formed keyhole or being captured by the solid-liquid interface or escaping from the free surface. Such phenomena manifest that the contributions to the processing quality and metallurgy quality of welded joints come from the complex melt flow behaviors, which are confirmed by a series of experiments.